Association of the Risk of Osteoarthritis and Hypertension in the Korean Adult Population Aged 40–59 in Pre- and Postmenopausal Women: Using Korea National Health and Nutrition Examination Survey 2012–2016 Data - Mikyung Ryu; Ji Sun Ha; Sol Lee; Weon-Chil Baek; Heejin Kimm; Ho Gym (International Journal of Hypertension)
Purpose. Previous studies reported the relation of osteoarthritis (OA) and hypertension (HTN) mostly in postmenopausal women. This study aimed to identify the association between OA and HTN in pre- and postmenopausal women. Methods. We used data of 4,627 middle-aged (40–59 years) women from the Korea National Health and Nutrition Examination Survey (KNHANES) from 2012 to 2016. Chi-square and t-test compared the characteristics of the participants. Binomial logistic regression was used to identify an association between OA and HTN under controlling covariates such as age, tobacco smoking, alcohol consumption, and obesity. Results. There were 1,859 participants with non-OA and menopause, 104 with OA and nonmenopause, and 375 with OA and menopause, respectively. The number of women with OA and HTN was 129. OA was significantly associated with HTN diagnosis in postmenopausal women under controlling covariates (odds ratio: 1.408, 95% CI: 1.092–1.815, p=0.008). However, this relationship was weakened in premenopausal women (odds ratio: 1.651, 95% CI: 0.950–2.869, p=0.075). Conclusion. In conclusion, women with HTN showed a distinct association with OA than the normotensives, and this relationship was more apparent among postmenopausal women. Further research is needed for a preventive approach.